FAKTOR-FAKTOR YANG MEMPENGARUHI KEJADIAN ABORTUS INKOMPLETUS DI RSUD DR. H. CHASAN BOESOIRIE TERNATE TAHUN 2014: FAKTOR-FAKTOR YANG MEMPENGARUHI KEJADIAN ABORTUS INKOMPLETUS DI RSUD DR. H. CHASAN BOESOIRIE TERNATE TAHUN 2014 - Nuzliati T Djama (UPPM Poltekkes Kemenkes Ternate, 2015)
Abstract : Abortus inkompletus is bleeding in early pregnancy where most of the products of conception have been out of the uterine cavity through the cervical canal it can be fatal to the mother such as bleeding, perforation, infection, and shock. This study aims to get a picture of maternal age, parity, education, history of abortus and marital status on the incidence of abortus inkompletus in hospitals Dr. H. Chasan Boesoeirie Ternate in 2014. Method this research is descriptive. The population in this study were 101 people and samples in this study were all women who had been treated with a diagnosis of miscarriage incompletus period January to August 2014. The data used are secondary data obtained from the hospital medical record Dr.H. Chasan Boesoirie Ternate. From the results, the incidence of abortus inkompletus much as 101 cases in 2014. Inkompletus most abortus cases were found at the age of 20-35 years by 74 cases (73,3%), parity 2-4 kids (49,5%), high school education or equivalent total of 64 cases (63,4%), not having abotus history (80,2%) and married status (84,2%). Looking at the data it will need the participation of various stakeholders from health, the family and the general public to prevent the factors that cause the incidence of abortus, such as counseling by health workers about the danger signs of pregnancy, the mother will need to plan and prepare for pregnancy by using contraception so as to regulate the child's birth and change mindsets through education must be made either through the school or outside the school on reproductive health so that they can establish a rational and personal responsibility, especially for the younger generation.